AFEKSI SEBAGAI KATALISATOR DALAM PENDIDIKAN KARAKTER DI SMP NEGERI 9 YOGYAKARTA - Wati, Nelly Setia; Abdillah Harahap, Khairul; Albilal, Ikram (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
The application of affection is reflected in various character education activities that support holistic character development. The implication of this research is the importance of integrating affection This study aims to examine the role of affection in character education at SMP Negeri 9 Yogyakarta, particularly in the process of internalizing character values and forming students' religious attitudes. A qualitative approach with a case study was used, involving teacher interviews and observation of interactions at school. Data analysis was conducted using a thematic approach. The results showed that affection plays a role in building positive relationships between teachers and students, which supports a sense of security, being valued and motivated, as well as the internalization of values such as honesty, responsibility, empathy and tolerance. Affection also influences students' religious attitudes through emotional experiences in religious learning and religious activities. in character education strategies to produce students who are smart and strong in morals, ethics and religion.